2010
DOI: 10.1016/j.juro.2009.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Resume Fraud: Unverifiable Publications of Urology Training Program Applicants

Abstract: Applicants had a low but still unacceptable rate of misrepresented publications and this trend in academic medicine is of great concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Research on the Urology Match has included why certain medical schools send more students into urology, 12 the competitiveness of matching, 1,13 participant experiences, 14,15 why medical students choose urology, 16 the cost of interviewing, 17,18 predicting success in residency 19 and a game theory perspective of the application process. 20 This research has shed light on the current strengths and limitations of the AUA RMP.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the Urology Match has included why certain medical schools send more students into urology, 12 the competitiveness of matching, 1,13 participant experiences, 14,15 why medical students choose urology, 16 the cost of interviewing, 17,18 predicting success in residency 19 and a game theory perspective of the application process. 20 This research has shed light on the current strengths and limitations of the AUA RMP.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that deliberate misrepresentation in CVs is becoming a growing problem (Wexler , Nosnik et al . ).…”
mentioning
confidence: 97%
“…It is likely too that these people will continue to exhibit unbecoming and unprofessional behaviour, in various ways, throughout their career (Nosnik et al . ).…”
mentioning
confidence: 97%
“…Although no studies have specifically evaluated pharmacy residency applicants, residency program directors and preceptors should be aware that several studies have found a high prevalence of misrepresentation among applicants to medical or surgical residency programs. [2][3][4][5] These studies have found frequent inaccuracies in professional association involvement 2 and a significant number of applicants misrepresenting publications. [3][4][5] Examples of publication misrepresentation found in these studies include the reporting of authorship of an article that does not exist, false claims of authorship of an existing article, and advancement of the applicant in the order of authors (e.g., listing oneself as first author when he or she was a middle author).…”
mentioning
confidence: 99%
“…[2][3][4][5] These studies have found frequent inaccuracies in professional association involvement 2 and a significant number of applicants misrepresenting publications. [3][4][5] Examples of publication misrepresentation found in these studies include the reporting of authorship of an article that does not exist, false claims of authorship of an existing article, and advancement of the applicant in the order of authors (e.g., listing oneself as first author when he or she was a middle author). Possible explanations for misrepresentation include the resident wanting to gain a competitive advantage and perceiving a low risk of being caught, as well as innocent misunderstandings or errors.…”
mentioning
confidence: 99%